2017
DOI: 10.1017/s1351324916000346
|View full text |Cite
|
Sign up to set email alerts
|

Citation function, polarity and influence classification

Abstract: Current methods for assessing the impact of authors and scientific media employ tools such as H-Index, Co-Citation and PageRank. These tools are primarily based on citation counting, which considers all citations to be equal. This type of methods can produce perverse incentives to publish controversial or incomplete papers, as mixed or negative reviews often generate larger citation counts and better indexes, regardless of whether the citations were critical or exerted minimal influence on the citing document.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
35
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 26 publications
0
35
0
Order By: Relevance
“…Citation polarity determines the attitudes of the citing authors toward the cited paper, which could be favorable (positive), unfavorable (negative) or neither of these (neutral). However, citation purposes refer to citers' reasons and motivation in citing documents (Hernández-Alvarez et al, 2017;Jha et al, 2017).…”
Section: Summarizing the Empirical Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Citation polarity determines the attitudes of the citing authors toward the cited paper, which could be favorable (positive), unfavorable (negative) or neither of these (neutral). However, citation purposes refer to citers' reasons and motivation in citing documents (Hernández-Alvarez et al, 2017;Jha et al, 2017).…”
Section: Summarizing the Empirical Resultsmentioning
confidence: 99%
“…For example, "use" can be seen in several studies Hernández-Alvarez et al, 2017;Jha et al, 2017) which happens to have a high frequency compared to other functions. "Use" has also been found to be among the most frequent verbs in different articles sections types (Bertin & Atanassova, 2014).…”
Section: Citation Function And/or Polaritymentioning
confidence: 99%
See 1 more Smart Citation
“…For example, R. Jha et al (2017) indicated that the most frequent citation function was "use" (17.7%), and that the accuracy of their proposed classifier in recognizing "use" (60%) was higher than that of other functions. "Use" was found to be mentioned quite frequently in most sections, specifically methods and introduction sections"… But on the other hand, I. Tahamtan & L. Bornmann (2019) stated that "low precision of the classification scheme in detecting citation functions" was mentioned in one of the works under analysis; while, according to another cited paper, "the issue with the studies that use automated data processing is that the classification schemes they propose for identifying citation functions do not yield reliable results (Hernández-Alvarez et al, 2017;Tahamtan & Bornmann, 2019).…”
Section: Resultsmentioning
confidence: 99%
“…Citation classification is the one approach of content-based citation analysis that aims to understand the influence of scientific literature on authors, such as the author's purpose regarding citing a paper or the function of a citation. However, identifying the key concepts in citation context automatically is complex and they are difficult to classify, because the differences among categories are too subtle and many categories make it hard to apply automatic methods, especially using linguistic markers [29][30]. Citation classification with three classes regularly refers to citation polarity [31].…”
Section: Automatic Citation Classificationmentioning
confidence: 99%